Trademark protection in the metaverse from a general EU trademark's perspective - Ziediņa, Kristīne (Riga Graduate School of Law, 2023)
This thesis researches the legal framework surrounding Non-Fungible Tokens (NFTs) in Web 3.0 or the Metaverse context. Due to their unique characteristics, NFTs require novel regulatory approaches, yet the decentralized nature of the blockchain system makes regulating this sphere difficult. The main objectives are to define NFTs, compare adopted definitions, evaluate the existing system, analyze case – law and adopted approaches by courts, and determine whether the EU trademark system needs to be adjusted. This thesis finds that legislators must reach a consensus on practical definitions to establish consistency in potential NFT-related laws. The existing IP regime is well-equipped to protect IP rights holders against infringements relating to NFTs. The current IP regime is sufficient not only in theory, but case-law analysis shows that it can also tackle real-life issues. Policy-makers need to guide the judiciary branch on how to interpret and apply existing laws.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Intellectual property law; Non-Fungible Tokens; Metaverse